Managing outsourcing projects - Jørgensen, Thomas (Henry Stewart Talks, 2019)
IT outsourcing, On-site, Cloud hosting, Due diligence, Contracting, Transition and transformation, Projects, Programs, Governance, Communications, Knowledge transfer, Program end